IMPACTS OF IMPORT TARIFFS AND NONTARIFF MEASURES ON INDONESIA’S TRADE PERFORMANCES OF ENVIRONMENTAL GOODS: A GRAVITY MODEL - Made Satriawan Mahendra; Akhmad Solikin (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
In 2011 leaders of Asia-Pacific Economic Cooperation (APEC) members pledged to reduce tariffs and nontariff barriers on goods and services related to environmental goods, known as APEC Environmental Goods List. In 2012 it was agreed that the member countries will reduce import tariff for the environmental goods to be maximum of 5% by 2015. The commitment is controversial since it is agreed as APEC commitment and hence nonbinding. However, since the tariffs are applied under Most Favored Nation principle, by definition the tariffs apply to all countries. This article aims at analyzing impacts of import tariffs and nontariff barriers for the environmental goods on Indonesia’s trade performances. In this study, the environmental goods include APEC Environmental Goods List and WTO Environmental Goods Core. The gravity model is used to explain variations in Indonesia’s exports and imports of 54 environmental goods to 18 trading partners. Data included in the analysis were obtained from secondary sources and were analyzed using fixed effect panel data regression. The results show that import tariffs do not affect import, while they affect export negatively. The nontariff measures affect positively to both import and export performances. Other variables, namely the gross domestic product and distance are significant and have influence as predicted by theory.JEL Classification: F10, F13, F14Keywords: APEC Environmental Goods List, Gravity model, Import tariffs, Nontariff barriers, Trade performance, WTO Environmental Goods Core List